Good citizenship and educated citizens: Social studies curricula comparison in Indonesia-England - Ines Alifah Wachidatun Chasanah; Anik Widiastuti (Inovasi Kurikulum, 2025)
The primary objective of social studies education is to develop citizens with civic skills and the ability to analyze social issues critically. This study aims to examine the comparative orientation of the objectives of the social studies curriculum in Indonesia, which emphasizes the formation of good citizenship character, and the orientation of the curriculum in England, which emphasizes the profile of educated citizens. This study is important to understand the philosophical differences underlying how each country conceptualizes social studies education. This study employs a content analysis method to objectively, systematically, and comprehensively analyze the contents of texts and curriculum documents in both countries. This study analyzed 11 curriculum documents from both countries, comprising five from Indonesia and six from England, using the Atlas.In their application, researchers analyzed the learning objectives, social studies content, and learning approaches using search keywords. The results of the content analysis of the curriculum documents indicate that the objectives of the social studies curriculum in Indonesia are oriented towards strengthening national identity through values, character, and morals (good citizenship), while in England, they are oriented towards developing students' capacity to play an active role in a democratic and global society (educated citizens). This suggests that the development of social studies in both countries aligns with the curriculum's needs and objectives.   Abstrak Tujuan utama dari pendidikan IPS adalah untuk membentuk warga negara yang memiliki keterampilan kewargaan dengan analisis kritis tehadap isu-isu sosial. Studi ini bertujuan untuk mengkaji perbandingan orientasi tujuan kurikulum IPS di Indonesia yang menekankan pada pembentukan karakter good citizenship dan orientasi tujuan kurikulum di Inggris yang menekankan pada profil educated citizens. Studi ini penting untuk memahami perbedaan filosofis yang mendasari bagaimana setiap negara mengkonseptualisasikan pendidikan IPS. Studi ini menggunakan metode analisis konten untuk menganalisis isi teks dan dokumen kurikulum di kedua negara secara objektif, sistematis, dan generalisis. Studi ini menganalisis 11 dokumen kurikulum dari kedua negara, yang meliputi 5 dokumen kurikulum di Indonesia dan 6 dokumen kurikulum di Inggris. Dengan menggunakan aplikasi atlas.ti, peneliti melakukan analisis terhadap tujuan pembelajaran, konten materi social studies, dan pendekatan pembelajaran dengan menggunakan kata kunci pencarian. Hasil analisis konten terhadap dokumen-dokumen kurikulum menunjukan bahwa tujuan kurikulum IPS di Indonesia berorientasi pada penguatan identitas bangsa melalui nilai, karakter, dan moral (good citizenship), sementara di Inggris berorientasi pada pengembangan kapasitas siswa dalam berperan aktif pada masyakarat demokratis dan global (educated citizens). Hal ini menunjukan bahwa pengembangan social studies di kedua negara bersifat kontekstual, sesuai dengan kebutuhan dan orientasi tujuan kurikulum yang ingin dicapai. Kata Kunci: kewarganegaraan yang baik; kurikulum IPS; studi perbandingan; warga negara yang terdidik